Digital Competence, Emotional Intelligence, Transformational Leadership, and Public Sector Performance in Regional Accounting and Finance Divisions: Job Satisfaction as a Mediator - Aida Irsyahma; Sriwidharmanely; Abdullah; Baihaqi; Husaini (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
The transition toward electronic-based government systems has disrupted traditional public sector administration, necessitating a re-evaluation of the determinants of bureaucratic performance. This study analyzes the impact of digital competence, emotional intelligence, and transformational leadership on employee performance, specifically investigating the mediating role of job satisfaction within the public sector accounting and finance environment of the Bengkulu Provincial Government. Utilizing a quantitative cross-sectional survey design grounded in Equity Theory, primary data were collected from 177 State Civil Apparatus personnel across 41 Regional Apparatus Organizations, selected through purposive sampling. The empirical data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrate that digital competence, emotional intelligence, and transformational leadership exert positive effects on job satisfaction. Job satisfaction, in turn, is positively associated with employee performance. Furthermore, mediation path analysis reveals that job satisfaction acts as a complementary mediator in the relationships between both digital competence and emotional intelligence and employee performance. The analysis also uncovers that job satisfaction serves as an indirect-only mediator (full mediation) in the relationship between transformational leadership and performance, indicating that leadership style alone cannot directly drive performance in highly regulated bureaucratic settings without first establishing employee satisfaction. As practical recommendations, government agencies should implement targeted technical training for specific platforms such as the Regional Government Information System (SIPD) and establish structured emotional intelligence and leadership coaching programs to optimize bureaucratic performance.